The penalties and scores by events, to predict victory and defeat according to when the contest ends in elite judo contests - Dopico-Calvo, Xurxo; Santos, Luis; Mayo , Xián; Carballeira , Eduardo; Clavel, Iván; Ceylam, Bayram; Kons, Rafael L.; Iglesias-Soler, Eliseo (Revista de Artes Marciales Asiáticas, 2024)
The main aim of this study was to ascertain whether the victory and defeat in the different types of the judo contest, in the elite male and female divisions, are associated to the occurrence of the penalties and scores of the first three events (changes in the scoreboard -either penalty or score-) of them. 2340 contests of the 2018, 2019 and 2021 World Judo Championships were analysed. The Pearson’s chi-squared test expressed that [1] shido-1 in the first event (EV1) of the contests that end before the regular time (BRT) and of those without considering when they end (OC) is associated to defeat for both sexes and, that [2] wazari-1 in the EV1 of the BRT and in the EV2 and EV3 of the BRT, of the contests with the duration extended beyond the regular time (EXT) and of OC is associated to victory for both sexes except in the EV2 of the EXT (only for male athletes in this case). Thus, it is suggested that the victory and defeat in the different types of the judo elite contests are associated with the occurrence of the penalties and scores of the first three events of them.